2017
DOI: 10.24252/bio.v5i1.3435
|View full text |Cite
|
Sign up to set email alerts
|

Induksi Umbi Mikro Kentang Secara In Vitro Pada Suhu Tinggi Dengan Beberapa Tuber Promoter

Abstract: Potato microtubers are the miniature of conventional seed tubers grown in the field. Producing potato microtuber in vitro at high temperature by applying many kinds of tuber promoting substances is similar to producing potato in the field at low elevation by applying the same tuber promoting substances. The objective of this research was to evaluate the performance of seven tuber promoters in inducing potato microtubers at high temperatures. Micro cuttings (6 weeks old) were grown at the liquid media of MS for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…3). These findings suggested that the PGR Mixture, containing retardant and cytokinin could suppress the negative effect of GA at high temperature, as reported previously [4,13,19]. In fact, exogenous application of cytokinin was reported to promote tuber growth [20] while that of GA3 inhibited tuber initiation [21].…”
Section: Pgr Mixturessupporting
confidence: 75%
See 3 more Smart Citations
“…3). These findings suggested that the PGR Mixture, containing retardant and cytokinin could suppress the negative effect of GA at high temperature, as reported previously [4,13,19]. In fact, exogenous application of cytokinin was reported to promote tuber growth [20] while that of GA3 inhibited tuber initiation [21].…”
Section: Pgr Mixturessupporting
confidence: 75%
“…Furthermore, the highest tuber weight was found when PGR mixture was applied in 3,4,5,6 WAE. These suggested that PGR mixture needs only to be applied in 3,4,5 WAE to promote tuber formation, but it needed another week (3,4,5,6 WAE) to promote tuber growth to yield the highest tuber weight (Table 3). It suggested that an additional application of PGR mixture (daminozide and BAP) in week 6 was very effective, because week 6 is the time when potato tuber starts to accumulate starch [12].…”
Section: Interaction Of Pgr Mixture and Application Timementioning
confidence: 99%
See 2 more Smart Citations